1991
DOI: 10.1002/jts.2490040307
|View full text |Cite
|
Sign up to set email alerts
|

Personal trauma and world view—are extremely stressful experiences related to political attitudes, religious beliefs, and future orientation?

Abstract: The study of the Hol (Holocaust)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 11 publications
(8 reference statements)
5
38
0
Order By: Relevance
“…A participant was considered a Holocaust survivor if she was in a country occupied by the Nazis during some or all of the years between 1939 to 1945, following Carmil and Breznitz (1991). While mass extermination did not begin until 1942 (Shanan, 1989), death was still omnipresent for Jews in the Nazi empire during the several preceding years.…”
Section: Participantsmentioning
confidence: 99%
“…A participant was considered a Holocaust survivor if she was in a country occupied by the Nazis during some or all of the years between 1939 to 1945, following Carmil and Breznitz (1991). While mass extermination did not begin until 1942 (Shanan, 1989), death was still omnipresent for Jews in the Nazi empire during the several preceding years.…”
Section: Participantsmentioning
confidence: 99%
“…Experiences of war violence are highly correlated with greater levels of social capital, community engagement, and peaceful political engagement. Carmil and Breznitz (1991) found that exposure to war led to greater political activism among groups such as Jewish Holocaust survivors and Palestinian victims of bombardment (Punamäki, Qouta, and El Sarraj 1997). Regarding El Salvador, Wood (2003) argued that government violence prompted its victims to support and even join opposition forces out of moral outrage.…”
Section: Political and Civic Participationmentioning
confidence: 99%
“…Results of studies are equivocal regarding trauma's negative or positive effects on an individual's religious beliefs and behaviors [12][13][14][15][16]. Harris et al developed an intervention called Building Spiritual Strength (BSS) to assist those who experienced military trauma in reducing PTSD symptoms by exploring spirituality as a source of support [17].…”
Section: Introductionmentioning
confidence: 99%